Prevalence of sun exposure and its associated factors in southern Brazil: a population-based study - Rodrigo Pereira Duquia; Ana Maria Baptista Menezes; Hiram Larangeira de Almeida Jr; Felipe Fossati Reichert; Iná da Silva dos Santos; Ricardo Lanzetta Haack; Bernardo Lessa Horta (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Sunlight exposure is responsible for a large number of dermatological diseases.OBJECTIVE: We estimated the prevalence of sunlight exposure and its associated factors in adults from southern Brazil in a cross-sectional, population-based study.METHODS:We investigated a representative sample of individuals aged ≥ 20 years (n=3,136). Sunlight exposure and its associated factors were evaluated in two distinct situations: at leisure time and at work. The time period investigated ranged from December 2004 to March 2005, comprising 120 days of the highest ultraviolet index in the urban area of the city of Pelotas, in southern Brazil. The participants were asked about sunlight exposure for at least 20 minutes between 10 A.M. and 4 P.M. The analysis was stratified by sex, and sunlight exposure was grouped into five categories.RESULTS:Among the 3,136 participants, prevalence of sunlight exposure at the beach was 32.8% (95% CI, 30.3 - 35.2) and 26.3% (95% CI, 24.2 28.3) among men and women, respectively. The prevalence at work was 39.8% (95% CI, 37.2 - 42.4) among men and 10.5% (95% CI, 9.1 - 12.0) among women. Age was inversely associated with sunlight exposure. Family income and achieved schooling were positively associated with sunlight exposure at leisure time and inversely associated with sunglight exposure at work. Self-reported skin color was not associated. Knowledge of any friend or relative who has been affected by skin cancer was positively associated with sunlight exposure among men at work.CONCLUSION:Despite the media campaigns on the harmful effects of excessive sunlight exposure, we found a high prevalence of sunlight exposure during a period of high ultraviolet index.